2015
DOI: 10.2320/matertrans.m2014352
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thickness and Crystallographic Orientation on Fatigue Life of Single-Crystalline Copper Foils

Abstract: Thickness effect on fatigue life of pure copper single-crystal foils with two different surface orientations, ð211Þ and ð5 11 1Þ, but with the same stress-axis orientation was investigated by means of S-N curve measurement and microstructural observation. Thicknesses of the foils were in range from 140 to 500 µm. Fatigue life of the ð21 1Þ specimen was much longer (by a factor of 1000) than that of the ð5 11 1Þ specimen within the given range of the foil thickness. The orientation dependence of fatigue life be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…found that double‐slip‐oriented single crystals had longer fatigue lives compared with single‐slip‐oriented single crystals. Kammuri et al . probed the t effect on the N f of pure Cu single‐crystal foils with two different orientations of [211¯] and [5 11¯1¯], and found that as t is in the range of 140–500 μm, thinner [211¯] and [5 11¯1¯] specimens have a shorter N f .…”
Section: Introductionmentioning
confidence: 99%
“…found that double‐slip‐oriented single crystals had longer fatigue lives compared with single‐slip‐oriented single crystals. Kammuri et al . probed the t effect on the N f of pure Cu single‐crystal foils with two different orientations of [211¯] and [5 11¯1¯], and found that as t is in the range of 140–500 μm, thinner [211¯] and [5 11¯1¯] specimens have a shorter N f .…”
Section: Introductionmentioning
confidence: 99%